Pentingnya Pendidikan Kewarganegaraan Juga Penerapan dan Relevansi dalam Kehidupan Di Era Teknologi Generasi Milenial - Elza Amalia Salsya Bani; Dinie Anggraeni Dewi (Syntax Idea, 2021)
The purpose of this study is to get an overview related to the application of relevance in life in the era of technology millennials. The method used in this study is qualitative method with descriptive research. The research instrument used uses interview guidelines, notes in the field. Data analysis techniques ranging from data collection, data reduction, to conclusion drawing. The result of this study is that the author states that millennials are a generation that is currently very vulnerable when not getting moral and religious education, even good and strong citizenship. This is because today's young generation is very vulnerable in believing information that is not yet clear validity, or commonly known as hoaxes, when the child is unable to distinguish between the original news and the fake one. If this is the case continuously, then Indonesia in the future will be prone to be divided, because its successors are easy to be pitted against if they cannot distinguish between the right and the not.